Neurorights and the Common Good: Christian Ethical Perspectives on Neurotechnologies, AI, and Human Rights - Messer, Neil (The review of faith & international affairs, 2025)
A wide array of current and emerging technologies combine neuroscience with artificial intelligence to collect, analyze, and exploit subjects’ brain data, modify their brain functions, and connect their brains to computers and other brains. While these technologies are said to offer many benefits, they also raise ethical concerns about identity, moral agency, privacy, human enhancement, and justice. In the face of these concerns, some have called for new “neurorights”—neurotech-specific human rights designed to protect humans’ interests from threats posed by these technologies—and these calls have found a response in current work by UNESCO. Should Christians and churches join others in advocating for new neurorights? Using the concept of the common good to frame the discussion, this article offers a Christian theological analysis of neurorights proposals, asking whether supporting them would be the most appropriate and effective way for Christian believers and communities to respond to the threats posed by some neurotech applications. The answer to this question will require prudential judgment, taking account of legal scholars’ evaluations of these proposals as well as the wisdom and experience of practitioners and activists.